Sovereign genes: wildlife conservation, genetic preservation, and Indigenous data sovereignty - Robbins, Paul; Hunt, Hilary Habeck; Pelegri, Francisco; Gilbert, Jonathan (Frontiers in Conservation Science, 2023)
The application of conservation genetics to wildlife preservation efforts are ongoing and promising. These involve the mobilization of a toolkit that ranges from monitoring the genetic diversity of rare species to more ambitious experiments in repopulating species experiencing genetic bottlenecks. All such efforts are predicated upon the deliberate and thoughtful preservation of existing genetic diversity. The history of genetic collection and conservation, however, for medical and health applications, is one that has repeatedly fallen into colonial habits, violated Native sovereignty, and sown distrust with Indigenous communities. Given the importance of Indigenous communities in the future of wildlife conservation, the future of conservation genetics is best assured through the honoring of Indigenous Data Sovereignty. This paper reviews the stakes of this question, reflects on the status of recent conservation genetics efforts relative to the question of Indigenous sovereignty, and lays out a preliminary set of principles for collaborative work on wildlife conservation employing genetic tools.